Finding One's Way on the Roads to Social Change: The Metamodel of the Impact of FOPH Communication Campaigns. (June 2016) - Kammer, Adrian; Niessen, Sebastian; Schmid, Lukas; Schwendener, Norina
Many theories and models attempt to explain the mechanisms underlying human behavior. In order to maintain an overview of the many aspects involved in communication campaigns, social marketing, and behavior change, the Swiss Federal Office for Public Health has created a metamodel of the impact of its campaigns. This metamodel does not claim to contribute any new findings to behavioral research. Its purpose is primarily to summarize the current state of research in the field in a comprehensive and comprehensible way, with reference to a range of relevant communications, social marketing, and behavior change theories. Dimensions addressed include strategy, processes, and impact, with the final dimension demonstrating the possible ranges of impact from individual to societal and from information to behavior. Social marketers and campaign planners may find this model useful as a planning and evaluation tool for campaigns, programs, or interventions that seek to increase awareness or change behavior. Its focus lies on communication campaigns, while also indicating the limits of campaign efficacy. It makes it clear that campaigns are most effective at the early stages of the behavioral change process, such as capturing attention, while other interventions are more effective at later stages.